Changes of glacier lakes using multi-temporal remote sensing data: A case study from India - Rai P.K.; Mishra V.N. (My University, 2025)
The present study used the potential of Landsat multispectral data and ASTER-DEM data to identify the changes of glacier lakes in part of Chandra basin and surrounding of Himachal Pradesh of India from 1989 to 2013. The Barashigri, Chotashigri, Hamtahand Parvati glacier are the major glaciers within the area. The Landsat data of TM (1989 and 2009), ETM+ (2001) and OLI-TIRS (2013) sensors having different band combinations were analysed to monitor variation in the glacier lakes and area of glaciers and terminus whereas ASTER-DEM data was used for relief information. Glaciers terminus and glacial lakes were identified and mapped using false-colour composites (FCC) with band combinations of red, near-infrared (NIR) and shortwave infrared (SWIR), and a true-colour composite of red, green and NIR, of Landsat TM/ETM+ images and normalized difference water index (NDWI) methods. It is observed that the number of lakes in the study area increased by 18.69% during the past 34 years while it was increased from 68 in 1989 to 89 in 2013. During the analysis, it is also found that the snow and glacier covered area within this period is also reduced from 1,317.39 to 1,125.59 km2.